E-leadership in nursing – a systematic review - Numanovic, Vanesa; Jalonen, Harri; Lindell, Juha; Jacobsson, Julia (Finnish Journal of eHealth and eWelfare, 2024)
Nurses and nurse leaders play a key role in healthcare digitalisation. While the volume of nursing leadership research has increased dramatically, empirical research on e-leadership in nursing remains limited. We believe this is the first systematic review of e-leadership among nurse leaders. Our purpose is to synthesise and describe existing research knowledge on e-leadership in nursing and to identify gaps in research knowledge. We conducted a systematic literature review guided by the framework suggested by Holly et al. (2017). We searched the CINAHL, Scopus, Web of Science, PubMed, Business Source Premier and Medic databases. The search yielded 1,968 records. We excluded 656 duplicates and 1,125 records by reference to the title and read 187 abstracts. We read 51 full texts, resulting in 12 records; we screened the reference lists of each of those and detected one more relevant record. The review includes 13 studies. Qualitative content analysis was utilised to analyse the data, leading to three main themes being identified: i) interpersonal relationships, ii) e-leadership and coping and iii) readiness for e-leadership and remote work. The main themes incorporated 12 sub-themes. The paper concludes by presenting several practical implications for nurse leaders and their organisations. The findings indicate a readiness for e-leadership among nurse leaders and for remote work among employees. There are several advantages but also many disadvantages regarding e-leadership in nursing. Nurse leaders need sufficient training in e-leadership as digitalisation is progressing in healthcare.